Characteristics of caring self‐efficacy in pediatric nurses: A qualitative study. Issue 3 (7th April 2015) - Alavi, Azam; Bahrami, Masoud; Zargham‐Boroujeni, Ali; Yousefy, Alireza
Abstract Purpose The present study was conducted to clarify pediatric nurses' characteristics of caring self‐efficacy. Design and Methods This study was conducted using a qualitative content analysis approach. The participants included 27 pediatric nurses and clinical instructors, selected purposively. Data were collected using semi‐structured interviews and were analyzed using the content analysis method. Results Data analysis generated four main themes as attributes of a self‐efficient pediatric nurse including: (a) professional communications; (b) management of care; (c) altruism; and (d) proficiency. Practice Implications Nursing managers and instructors can use these results to help develop nurses' empowerment and self‐efficacy, especially in pediatric care.